(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Auxetic textile materials have become a point of developed knitted structures produced using high performance yarns and showing strong auxetic effects. The Negative Poisson Ratio based on Weft knitted fabric have huge potential for applications, especially in personal protection materials like bulletproof vest, and many industries application such as airspace, automobile, and so on. The present work reports auxetic structures using polypropylene filament yarn through weft knitted technology. The polypropylene filament yarn were knitted on a 5-gauge flat knitting machine (Passap Deumatic 80), using a 2-cam system with a pattern based on a (rib knitting) structure on the face and back loops. Three types of different loop length with same structural (fisherman’s rib) are used (LL3, LL4, and LL5). The effected of different Loop length on negative Poisson’s ratio (NPR) was investigated in the wale and courses direction. The results show that all knitted fabrics have the NPR effect,for the both direction (wale and course). It was observed that NPR improved strongly with the increase in loop length of knitted structures.